CrM : are managers aware of what this tool means? - Miranda, Mafalda Gonçalves Martins (2021)
The purpose of this study is to decode what managers think about Cause Related Marketing (CrM) campaigns. Through the application of the UTAUT model and data collection through in-depth interviews to managers, it is planned to unveil the level of acceptance and use concerning CrM. The CrM benefits recognized from the perspective of managers are mainly related to the increase of reputation and image of the company, making it possibile to differentiate and increase it notoriety. However the social nature of this tool is what weights the most on the decision of managers, since they recognize that being socially responsible is a competitive factor nowadays. The greatest constrictions are related to the efforts on the implementation of the campaign and with the consumer’s scepticism, especially in transactional campaigns. There is a misunderstanding between the CrM concept and purely philanthropic marketing, which can somehow inhibit managers from recognizing the potential of this tool. Regarding CrM use, the position of managers show a clear concern about the importance of harmonising values between the company and the cause, betting on long-term campaigns with transparent communication and investing on the process of planning, implementing and monitoring campaigns in order to improve their performance.